Spirulina platensis Inclusion Reverses Circulating Pro-inflammatory (Chemo)cytokine Profiles in Broilers Fed Low-Protein Diets - Mullenix, Garrett J.; Greene, Elizabeth S.; Emami, Nima K.; Tellez-Isaias, Guillermo; Bottje, Walter G.; Erf, Gisela F.; Kidd, Michael T.; Dridi, Sami (Frontiers in Veterinary Science, 2021)
Proteins are considered the most expensive nutrients in commercial modern broiler production, and their dietary inclusion at low levels is pivotal to minimize feed costs and reduce nitrogen waste. The quest for environmentally-friendly source of proteins that favor formulation of low protein diets without compromising broiler health, welfare, and growth performance have become a hotspot in nutrition research. Due to its high protein content, the natural growing Spirulina microalgae is considered a promising nutrient source. The purpose of the present study was, therefore, to determine the effects of Spirulina supplementation on liver bacterial translocation, hematological profile, and circulating inflammatory and redox markers in broilers fed a low-protein diet. One day-old Ross 708 male broilers (n=180) were randomly assigned into one of three experimental treatments: standard diet as a control, low protein diet, and low protein diet supplemented with 100 g/kg of Spirulina. Target molecular markers were measured in the peripheral blood circulation using real-time quantitative PCR. Reducing dietary proteins increased bacterial translocation and systemic inflammation as indicated by proportions of basophils among blood leukocytes. The expression levels of circulating pro-inflammatory cytokines (IL-3, IL-6, IL-4, IL-18, and TNFα), chemokines (CCL-20), and NLRP3 inflammasome were significantly upregulated in birds fed the low protein diet compared to the control. Inclusion of Spirulina reversed these effects, which indicates that Spirulina reduces systemic inflammation- and bacterial translocation-induced by low protein diet and could be a promising alternative protein source in poultry diets.